PERTUMBUHAN DAN HASIL CABAI RAWIT (CAPSICUM FRUTESCENS L.) PADA DOSIS TRICHODERMA, SP. DAN PUPUK ORGANIK PETROGANIK - I WAYAN SUKASANA; ANAK AGUNG GEDE PUTRA; PUTU EKA APRIASTUTI; I GUSTI AYU SURYA UTAMI DEWI (GANEC SWARA, 2024)
Cayenne pepper (Capsicum frutescens L.) is a plant that is commonly cultivated in Indonesia. The research aims to determine the highest growth and yield of cayenne pepper plants at a dose of Trichoderma, sp. and doses of petroganic organic fertilizer. Conducted at Tempek Subak Jangkahan, Subak Gede Bungan Kapal, Tunjung Village, Tabanan from 8 December 2022 – 24 April 2023. The design used was a randomized block, namely combined treatment. Trichoderma dosage, sp. is the first factor with three dose levels, namely without trichoderma (T0), 10 kg.ha-1 trichoderma,sp (T1) and 20 kg.ha-1 trichoderma,sp (T2). The second factor is the dose of petroganic organic fertilizer consisting of four dose levels, namely 0.5 t petroganic organic fertilizer. ha-1 (G1), petroganic organic fertilizer 1 t. ha-1 (G2), petroganic organic fertilizer 1.5 t. ha-1(G3) and 2 t petroganic organic fertilizer. ha-1 (G4). The combination treatment was repeated 3 times. The results showed that the interaction between the dose of Trichoderma ,sp and petroganic organic fertilizer showed no significant interaction (P≥0.05). The Trichoderma,sp dose was able to increase plant height, number of productive branches, total fruit harvest weight per plant, number of harvested fruit per plant with the highest yield at a dose of 20 kg.ha-1. Dosage of Trichoderma, sp 20 kg.ha-1. (T2) plant productivity per hectare was significantly higher by 7.76% compared to without Trichoderma dose (T0), namely 6.94 tonnes. The administration of Trichoderma,sp significantly (P<0.05) reduced the number of plants that died wither. The total weight of fruit harvested per plant significantly increased in the 1.5 ton petroganic dose treatment. ha-1, is 437.93 g, petroganic dose 2 tons. ha-1 can significantly (P<0.05) increase stem diameter, number of productive branches, number of leaves, number of fruit per plant